The antioxidant properties of garlic compounds: allyl cysteine, alliin, allicin, and allyl aisulfide - Chung, Lip Yong (Mary Ann Liebert, 2006)
Garlic and garlic extracts, through their antioxidant activities, have been reported to provide protection against free radical damage in the body. This study investigated antioxidant properties of garlic compounds representing the four main chemical classes, alliin, allyl cysteine, allyl disulfide, and allicin, prepared by chemical synthesis or purification. Alliin scavenged superoxide, while allyl cysteine and allyl disulfide did not react with superoxide. Allicin suppressed the formation of superoxide by the xanthine/xanthine oxidase system, probably via a thiol exchange mechanism. Alliin, allyl cysteine, and allyl disulfide all scavenged hydroxyl radicals; the rate constants calculated based on deoxyribose competitive assay were 1.4-1.7 X 10(10), 2.1-2.2 X 10(9), and 0.7-1.5 X 10(10) M-1 second(-1), respectively. Contrary to previous reports, allicin did not exhibit hydroxyl radical scavenging activity in this study. Alliin, allicin, and allyl cysteine did not prevent induced microsomal lipid peroxidation, but both alliin and allyl cysteine were hydroxyl scavengers, and allyl disulfide was a lipid peroxidation terminator. In summary, our findings indicated that allyl disulfide, alliin, allicin, and allyl cysteine exhibit different patterns of antioxidant activities as protective compounds against free radical damage.